2017
DOI: 10.1088/2058-8585/aa5ef9
|View full text |Cite
|
Sign up to set email alerts
|

Printable cellulose-based electroconductive composites for sensing elements in paper electronics

Abstract: Conductive flexible hydrogel composites were printed on paper substrates using a functional ink, which was designed and formulated for screen-printing. The inks were prepared using abundant and eco-friendly materials by blending carbon fibers into the matrix of a water-soluble cellulose derivative, carboxymethyl cellulose. For an optimal concentration of carbon fibers (10 wt.%), the printed patterns exhibit a sheet resistance of around 300 Ω/sq without any post-printing annealing process. The resistance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 54 publications
0
53
0
Order By: Relevance
“…Additionally, barrier layers or so-called "pre-coatings" might be required to separate the top coating from the paper substructure. For this purpose, resins [28], polyethylene [26] or other polymer-based materials [25] are used. Despite the obvious advantages of coating, it is an additional time-and resource-consuming processing step that increases the resulting material price.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, barrier layers or so-called "pre-coatings" might be required to separate the top coating from the paper substructure. For this purpose, resins [28], polyethylene [26] or other polymer-based materials [25] are used. Despite the obvious advantages of coating, it is an additional time-and resource-consuming processing step that increases the resulting material price.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of wireless passive LC sensors is that it enables efficient detection of signals wirelessly without using additional power sources like batteries . Cellulose‐based materials have been developed and utilized to make eco‐friendly flexible sensors . The LC printed with the cellulose‐based conductive ink of this study has its merits of being disposable, biocompatible, and eco‐friendly.…”
Section: Coefficients For Modified Wheeler Expressionmentioning
confidence: 99%
“…The high specific surface caused by the ultrafine 3D BC network structure greatly enhanced the overall sensitivity of the sensor. Beside simple pouring or casting cellulose-based films on a carrier substrate, Barras et al 55 prepared conductive printing ink by blending carbon fibers (CFs) in the CMC. Wang et al 49 demonstrated the application of cellulose nanocrystals (CNCs) as a component in conductive composite based on hybridized nanocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…Hashim and Hadi 52 published a new type of cellulose nanocomposite with titanium carbide (TiC) nanoparticles, while Chani et al 53 fabricated humidity sensor based on cellulose acetate (CA) composite with copper oxide (CuO) nanosheets and Ma et al 54 mixed hydroxyethyl cellulose (HEC) with multiwalled carbon nanotubes (MWCNTs) to form humidity sensing composite film on a ceramic substrate. Beside simple pouring or casting cellulose-based films on a carrier substrate, Barras et al 55 prepared conductive printing ink by blending carbon fibers (CFs) in the CMC. This was then used for screenprinting of humidity sensing elements on paper.…”
Section: Introductionmentioning
confidence: 99%